Tip toeing through the raindrops : the exercise of sovereignty in the Caribbean Community - Benn, Denis ([CCS] [Georgetown]GY, 2009)
Attempts to provide greater conceptual clarity on the nature of the relationship between sovereignty, intergovernmentalism and supranationality, with special reference to the requirements of regional integration arrangements such as CARICOM.